Ultrasonographic monitoring of the fetal growth of common seals (Phoca vitulina vitulina) - Gili C; Papini L; Romagnoli S.; VANNOZZI, IACOPO (2006)
Three captive female common seals (Phoca vitulina vitulina) were monitored ultrasonographically during five pregnancies. Pregnancy was diagnosed in the third month and fetal monitoring was continued until parturition. The ultrasound measurements were made with the active collaboration of the animals by training them to cooperate with the procedure.